Bronchial Arteries Embolization in Tuberculosis-Related Recurrent Hemoptysis with Complete Right Lung Atelectasis: A Case Report - Yulia Devina Suci Kusumastrini; Ariani Permatasari (Jurnal Respirasi, 2022)
Introduction: Hemoptysis is an emergency condition with high morbidity and mortality which requires immediate treatment. Active tuberculosis (TB) and post-tubercular sequelae can result in hemoptysis with the most common source is from bronchial artery.Case: We reported a 22-year-old man who presented with shortness of breath and recurrent hemoptysis. A chest X-Ray showed total atelectasis right lung due to obstructive airway. After aspiration clotting blood in bronchus and instillation adrenalin with fiber optic bronchoscopy, the atelectasis totally disappeared. Computed tomography angiography (CTA) showed prominent vascular lesions from the apical right pulmonary artery, right brachialis artery, and branch of the posterior intercostal artery. The patient was referred to the interventional unit of the radiology department in Dr. Soetomo General Hospital and underwent bronchial artery embolization. After this procedure, his symptoms resolved completely and he was discharged after a week with 2nd category anti-tuberculosis drugs (ATD). 6 months of follow-up, he no longer experienced hemoptysis.Conclusion: Recurrent hemoptysis needs optimal management, including diagnostic with chest radiography, CT and bronchoscopy. Treatment with bronchoscopy and bronchial artery embolization will reduce mortality and morbidity in patients with hemoptysis.